In vitro study of potential antibacterial pometia pinnata leaf extract in Neisseria gonorrhoeae - Widayani, Gandi Ari Savitri; Anwar, Muhammad Choiroel; Sudirman, Sudirman (MEDISAINS, 2021)
Background: Gonorrhea cases experiencing antibiotic resistance are increasing due to inadequate treatment or failure to contribute to an increase in antibiotic resistance cases; WHO suggests adding herbal therapy treatment methods is expected to minimize the occurrence of drug resistance as much as possible. Previous studies that have been carried out using other herbal plants have not shown any potential to inhibit the growth of Neisseria gonorrhoeae bacteria, seen from the amount of extract concentration and the dosage and content of the compounds in the contents monitoring the time.Objective: To analyze the difference in the effect of various concentrations of Matoa Leafs Extract (Pometia Pinnata) compared to 500mg Levofloxacin on the increase in the growth inhibition of Neisseria gonorrhoeae.Methods: This is true-experimental research with a post-test-only control group with a randomized design. The sample in this study was the microorganism Neisseria gonorrhoeae obtained through vaginal swabs in 2 females (FSW) positive for Gonorrhea by gram staining and microscopic examination and culture on Chocolate Agar Plant (CAP) media. The culture was then suspended in CAP media. Matoa Leaf extract concentration of 100%, 80%, 60%, 40%, 20%, positive control with Levofloxacin 500 mg and negative control with distilled water with four replications and monitoring in 24 hours, 48 hours, 72 hours, and 96 hours. Data analysis used Kruskal-Wallis, Mann-Whitney, and cohen's test. Result: Levofloxacin 500mg in inhibiting Neisseria Gonorrhoeae bacteria is very effective, and Matoa Leaf extracts 60% and 40% P=0,026 have a strong enough potential to inhibit the growth of Neisseria gonorrhoeae bacteria with the same potential strength. The cohen's test 1.4 effect the levofloxacin 500mg provides a significant influence inhibiting Neisseria Gonorrhoeae.Conclusion: Matoa Leaf extract 60%, and 40% have solid antibacterial potential, although not as strong as Levofloxacin 500mg.